International legal initiatives on diversified attraction of monetary and financial flows to the Republic of Kazakhstan - Sarsembayev, D.M. (Bulletin of the Karaganda University “Law Series”, 2022)
In this scientific article, the author formulates international legal initiatives to attract monetary and financial flows to the economy of the Republic of Kazakhstan. The article begins with an analysis of historical monetary and commodity turnover, which allows tracking the logic of monetary and financial movements up to the present. One of the international legal means of attracting monetary and financial flows to Kazakhstan could be the organization of trade tourism centers, which will need to be created in all regions of the country adjacent to neighboring states. Another international legal way could be to provide some territories of the country for long-term lease to other states, іn the territory of which it is possible to create enterprises for the production of goods for the whole world, as well as to create financial institutions to attract capital to the leased territory and Kazakhstan. The third direction could be the labor migration of Kazakhstani citizens organized by Kazakhstan to the leading cities of the world, whose wages in foreign currency could serve their families and the economy of Kazakhstan. The creation of national Internet platforms, based on which citizens of Kazakhstan would provide services to citizens and organizations of other countries on a paid currency basis, could also contribute to attracting the currency mass to the country.